Physicochemical and biopharmaceutical characterization of novel Matrix-Liposomes - Binnefeld, Michael; Fritz, Sandra; Balzer, Viktor; Skalická, Veronika; Witzigmann, Dominik; Kauczor, Hans-Ulrich; Fricker, Gert; Salomon, Johanna J. (European journal of pharmaceutics and biopharmaceutics, 2020)
Matrix-Liposomes (MLs) are a very promising solid oral drug delivery system; however, data on their interaction with biological membranes are not available. Here, we describe the quality of MLs manufactured by dual centrifugation. MLs were prepared with a Z-average range of 139 to 160nm and a PDI of 0.18 to 0.25. To investigate the effect of MLs on intestinal tissue (with and without mucolytic treatment), we then established an ex vivo rat intestine model. The integrity of the epithelial membranes of rat intestine was not affected by the incubation with MLs without or with pre-mucolytic treatment. Tissue samples were also analysed for changes in P-glycoprotein (P-gp) expression and function. The net secretion of the P-gp substrate Rh123 across the rat duodenum was increased in the presence of MLs. To summarize, MLs do not affect intestinal epithelial integrity, although they impact Rh123 secretion. In future, these novel MLs have to be further evaluated for proficient intestinal drug delivery.
Gesehen am 13.08.2020